PENGARUH SKEPTISME PROFESIONAL, INDEPEDENSI KOMPETENSI, PENGENDALIAN INTERNAL DAN BEBAN KERJA TERHADAP KEMAMPUAN AUDITOR MENDETEKSI KECURANGAN (Studi Empiris Pada BPKP Perwakilan Provinsi Riau) - Fajar, Yundeya Muhammad; M, Rasuli; Volta, Diyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This research aims to know and analyze about: (1) the influence of professional skepticism on the ability of auditors to detect cheating, (2) the influence of independence on the ability of auditors to detect cheating, (3) the influence of competencies on the ability of auditors to detect cheating, (4) the influence of internal control on the ability of auditors to detect fraud in riau province. The respondents in the study were 58. This study used questionnaires in its data collection.. Data analysis is used by multiple linear regressions. The results of this study prove professional skepticism has a positive effect on the ability of auditors to detect fraud. Independence has a positive effect on the auditor's ability to detect fraud. Competence has a positive effect on the ability of auditors to detect fraud. Internal control has a positive effect on the ability of auditors to detect fraud, workload negatively affects the ability of auditors to detect fraud.Keywords: Professional Skepticism, Independence, Competence, Internal Control, Workload, Auditors' Ability To Detect Fraud.